Efek Bawang Bombay dalam Menurunkan Kadar Gula Darah pada Tikus Putih - Yunesya Elfira Dewi; Meida Nugrahalia; Ida Fauziah (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
The research was conducted to observe the effect of Allium cepa L in reducing blood glucose level in white rat (Rattus novergicus). Treatments were consist of 2 ml and 4 ml of Allium cepa L and aquadest was used as treatment for control group. The result showed significant effect of both treatments using Allium cepa L compared to control group. Thus concluded that Allium cepa L has a good efficacy in reducing blood glucose level. But posthoc test using LSD did not show any difference between treatment groups of 2 ml and 4 ml.